2012
DOI: 10.1093/eurjhf/hfs008
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute pulmonary oedema and cardiac arrest secondary to intermittent electrical dyssynchrony: a role for cardiac resynchronization despite preserved left ventricular function

Abstract: Recurrent pulmonary oedema with no obvious precipitant can prove difficult to treat in patients with preserved left ventricular (LV) systolic function. This report describes the novel use of cardiac resynchronization therapy (CRT) in the prevention of acute pulmonary oedema precipitated by intermittent electrical dyssynchrony in a patient with preserved LV systolic function.Acute pulmonary oedema remains a common presentation to emergency departments. The aetiology of the pulmonary oedema is not always apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…An electrophysiologic study confirmed the development of LBBB only with pacing greater than 140 BPM. In another case report, a 75-year-old woman experienced 2 episodes of respiratory arrest and pulseless electrical activity in the setting of “flash” pulmonary edema 8 . Imaging studies revealed preserved systolic function; exercise testing eventually induced sinus tachycardia with LBBB and recurrent pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…An electrophysiologic study confirmed the development of LBBB only with pacing greater than 140 BPM. In another case report, a 75-year-old woman experienced 2 episodes of respiratory arrest and pulseless electrical activity in the setting of “flash” pulmonary edema 8 . Imaging studies revealed preserved systolic function; exercise testing eventually induced sinus tachycardia with LBBB and recurrent pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…The term atrial resynchronization therapy can be coined for this therapy and might be new in the arsenal of treatments for HFPEF and to prevent AF . In addition to atrial resynchronization, ventricular resynchronization can also be effective in patients with HFPEF . Biventricular pacing might be the preferred strategy in any patient that needs continuous ventricular pacing .…”
Section: Defibrillators and Resynchronization Therapymentioning
confidence: 99%
“…89 In addition to atrial resynchronization, ventricular resynchronization can also be effective in patients with HFPEF. 90 Biventricular pacing might be the preferred strategy in any patient that needs continuous ventricular pacing. 7 Whether this is true for all patients remains unknown.…”
Section: Defibrillators and Resynchronization Therapymentioning
confidence: 99%